Determinants of Nurses’ Job Satisfaction: A Cross-Sectional Study in an Indonesian Public Hospital - Aida Rachmiana; Suryadi Suryadi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Job satisfaction is a key element in achieving optimal performance and quality of care among nurses, particularly in public healthcare institutions where structural and psychological challenges often intersect. This study aims to identify and analyze six workplace factors such as job characteristics, promotion opportunities, working conditions, salary, supervision, and peer relationships that influence nurses' job satisfaction at Meuraxa General Hospital in Banda Aceh, Indonesia. A quantitative, cross-sectional study was conducted involving 77 civil servant nurses selected through total sampling. Data were collected using a structured questionnaire and analyzed using bivariate and multivariate linear regression. The results revealed that job characteristics, salary, and peer relationships had a statistically significant positive effect on job satisfaction in both bivariate and multivariate models. In contrast, promotion, supervision, and working conditions were significant only in the bivariate analysis, suggesting their influence diminishes when analyzed alongside stronger variables. The study concludes that meaningful job design, fair compensation, and collegial support are essential drivers of job satisfaction in the nursing profession. These findings offer valuable input for hospital management and policymakers to enhance nurse engagement, reduce turnover, and improve service quality. Future research may expand to include qualitative perspectives and explore these dynamics across various healthcare settings in Indonesia.